Reading the Real: An Illustrated Tour of Montreal’s Marché Jean-Talon - Musgrave, Sarah (Cuizine, 2008)
AbstractThe slogan of Montreal's Marché Jean-Talon is "When country comes to town."  An afternoon stroll through the city's largest public food market suggests that the word applies in both senses: country, as in the rural landscape, and country, as in the nations of the world. In surveying the cornucopia of place-based messages that greet potential shoppers, this paper positions the farmers’ market as a site for the consumption of authentic and authenticated foods, and thus a suitable microcosm for the exploration of larger issues related to consumer trends towards provenance purchasing, origin labelling, and the promotion of place as the primary marker of alimentary authenticity in the wider food marketplace.